Neisseria meningitidis Serogroup Y Sequence Type 1466 and Urogenital Infections - Sebastiaan J. van Hal; Thomas Le; Frances Jenkins; Ratan L. Kundu; E. Athena Limnios; Lucy A. McNamara; Shalabh Sharma; Ellen N. Kersh; Monica M. Lahra (Emerging Infectious Diseases)
Neisseria meningitidis is a common commensal bacterium of the nasopharynx that can cause invasive meningococcal disease (IMD). In comparison, N. gonorrhoeae is always a pathogen usually limited to mucosal sites. However, increased evidence for overlapping clinical syndromes is emerging. We compared N. meningitidis samples from a urogenital outbreak in Australia with sequences from the United States and other countries. We conducted phylogenetic analyses to assess relatedness and examine for genomic changes associated with meningococcal adaptation; we collated a total of 255 serogroup Y (MenY), sequence type (ST) 1466 isolate assemblies. Most urogenital isolates originated from Australia; those isolates formed a distinct clade, most closely related genomically to recent US IMD isolates. No specific genomic changes suggested niche adaptation or associated clinical manifestations. The MenY ST1466 N. meningitidis isolates circulating in Australia and the United States are capable of causing both urethritis and invasive meningococcal disease.